Policy For Providing Sanctions For Students Who Are Late To Come To The Mosque At The Darussalam Sempurna Bin Baz 9 Branch Musi Rawas Islamic Boarding School - Azis, Abdul; Tuanto, Eko (Early Publishing, 2024)
This research aims to identify the policy of providing sanctions for students who are late in coming to the mosque at the Darussalam Pesantren Perfect Bin Baz 9 Musi Rawas Branch, as well as analyzing the impact of implementing sanctions on the discipline and quality of the students' worship. The research method used is descriptive qualitative with data collection through observation, interviews and documentation. The results of the research show that giving sanctions in the form of prayers in the first row for students who are late is effective in increasing students' discipline and obedience in carrying out worship. It is also hoped that this policy can provide guidance to students to value time more and prioritize worship. This research provides recommendations for improving and developing discipline policies in Islamic boarding schools to create a more orderly and orderly environment.